Collagen in food and beverage industries - Hashim, Puziah; Mohd Sofberi, Mohammad Ridzwan; Bakar, Jamilah; Mat Hashim, Dzulkifly (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
This paper reviews the structure, function and applications of collagens in food industry. Collagen is the most abundant protein in animal origin. It helps maintaining the structure of various tissues and organs. It is a modern foodstuff and widely used in food and beverage industries to improve the elasticity, consistency and stability of products. Furthermore, it also enhances the quality, nutritional and health value of the products. Collagen has been applied as protein dietary supplements, carriers, food additive, edible film and coatings. Therefore, this paper will review the functions and applications of collagen in the food and beverage industries. The structure and composition of collagen are also included.